A new species of Freycinetia Gaudich. (Pandanaceae; Freycinetoideae) from Tidore Island, Moluccas, Indonesia. - Ary Prihardhyanto Keim (BRIN Publishing (Penerbit BRIN), 2013)
Freycinetia tidorensis A.P. Keim is newly described from Tidore Island, Moluccas. This new species is morphologically similar to F. devriesei Solms but differs in the number of stigmatic remains. In F. devriesei the number is 3 to 6, never less than 3; whereas in Freycinetia tidorensis 1 to 2, never more than 2.